Teacher’s Perceptions of the English Teacher Competences of Senior High School in Pangkep - Sri Fausyia; Syarifuddin Dollah; La Sunra (PT ARRUS Intelektual Indonesia, 2024)
The objective of this study is to find out teachers' perceptions of English teachers' competence in senior high schools in Pangkep. This study uses a qualitative method. The population of this study is teachers in senior high schools in Pangkep, with the sample consisting of English teachers in SMAN 2 Pangkep, SMAN 9 Pangkep, and SMAN 10 Pangkep. The research instrument used is interviews. The results show that English teachers' perceptions of competence include four aspects: professional competence, personality competence, pedagogical competence, and social competence, all of which are important and interrelated to carry out tasks effectively and professionally.